THE IMPACT OF USING MODERN ALSINTAN ON WET-RICE FARMING IN MARADEKAYA VILLAGE, BAJENG SUB-DISTRICT, GOWA DISTRICT - Arwati, Sitti Arwati; Reni Fatmasari Syafruddin; Muh.Yusri. K; Amanda Patappari Firmansyah (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to assess the impact of the use of modern Alsintan on rice farming. rice farming in Maradekaya Village, Bajeng District, Gowa Regency. The informant retrieval technique in this study used the purposive sampling method, where informants were determined intentionally. The level of adoption of modern agricultural machinery in Maradekaya Village is quite high, including the use of 4-wheel tractors, rice transplanting machines, and rice harvesting machines, which certainly greatly help the lives of farmers. The impact of using modern agricultural machinery brings many changes to the activities of rice farmers, such as a reduction in time and labor, a reduction in capital, and an increase in productivity that is more profitable than before using agricultural machinery technology. Farmers can more easily divide their time for other work besides farming with modern agricultural machinery. In addition, modern agricultural machine tools (Alsintan) make rice farmers' work time more efficient than before the existence of this technology in Maradekaya Village.